Econet Base Station Fault Monitoring and Planned Maintenance Scheduling System - Masvanhise, Gerald (Midlands State University, 2017)
The manual Fault Monitoring System lacks immediate retrieval of information such as base station fault history and diagnosis , the system lacks prompt updating for example system user status, when schedules to maintain base station changes; the system does not produce reports which assist management in decision making. The analysis phase saw the researcher using various data gathering methodologies which included observations, questionnaires and interviews among others. From the analysis phase the researcher proposed development of a fault monitoring and planned maintenance scheduling system that keep base station faults, which allows technicians to send fault names and receive instant solutions on their mobile numbers, the systems allows technicians also to take part in system polls and sends maintenance schedules to registered technicians. A detailed study was carried out and it resulted feasible to design the system and an in-house development solution was recommended. Various designing tools were used which included Wamp Server and Adobe Dreamweaver. The system was successfully implemented and parallel changeover was the recommended changeover strategy after weighing its many advantages over other strategies. Perfective maintenance strategy which allows for continual improvement of the system was chosen.